Pemanfaatan Jurnal Terakreditasi Nasional Dalam Penulisan Tugas Akhir Oleh Mahasiswa UIN Sumatera Utara - Rahmah, Siti; Sayekti, Retno; Syam, Abdi Mubarak (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses the utilization of nationally accredited journals in writing final assignments by UIN North Sumatera students. The objectives to be achieved from this research are to find out the utilization of nationally accredited journals in writing final assignments by UIN North Sumatra students and the obstacles faced by students in utilizing nationally accredited journals. The research conducted by researchers used descriptive research with a qualitative approach. The data collection methods used are observation, interview and documentation. In this study, the informants were FIS students class of 2019. The results of this study indicate that most students do not use accredited journals because of the lack of promotion by the library so that information is not evenly distributed throughout the academic community. The obstacles that prevent students from using nationally accredited journals are language, promotion and lack of student awareness. The implication of this research is that it is necessary to conduct user education by emphasizing the introduction of nationally accredited journals and how to access them.